Mining legacy across a wetland landscape: high mercury in Upper Peninsula (Michigan) rivers, lakes, and fish. Issue 4 (29th March 2018) - Kerfoot, W. Charles; Urban, Noel R.; McDonald, Cory P.; Zhang, Huanxin; Rossmann, Ronald; Perlinger, Judith A.; Khan, Tanvir; Hendricks, Ashley; Priyadarshini, Mugdha; Bolstad, Morgan
Abstract : A geographic enigma is that atmospheric deposition of mercury is low and declining in the Upper Peninsula although total mercury (THg) and (MeHg) levels are high in waters and fish. Abstract : A geographic enigma is that present-day atmospheric deposition of mercury in the Upper Peninsula of Michigan is low (48%) and that regional industrial emissions have declined substantially ( ca. 81% reduction) relative to downstate. Mercury levels should be declining. However, state (MDEQ) surveys of rivers and lakes revealed elevated total mercury (THg) in Upper Peninsula waters and sediment relative to downstate. Moreover, Western Upper Peninsula (WUP) fish possess higher methyl mercury (MeHg) levels than Northern Lower Peninsula (NLP) fish. A contributing explanation for elevated THg loading is that a century ago the Upper Peninsula was a major industrial region, centered on mining. Many regional ores (silver, copper, zinc, massive sulfides) contain mercury in part per million concentrations. Copper smelters and iron furnace-taconite operations broadcast mercury almost continuously for 140 years, whereas mills discharged tailings and old mine shafts leaked contaminated water. We show that mercury emissions from copper and iron operations were substantial (60–650 kg per year) and dispersed over relatively large areas. Moreover, lake sediments in the vicinity of mining operations have higher THg concentrations. Sediment profiles from the Keweenaw Waterway show that THg accumulation increased 50- to 400-fold above modern-day atmospheric deposition levels during active mining and smelting operations, with lingering MeHg effects. High MeHg concentrations are geographically correlated with low pH and dissolved organic carbon (DOC), a consequence of biogeochemical cycling in wetlands, characteristic of the Upper Peninsula. DOC can mobilize metals and elevate MeHg concentrations. We argue that mercury loading from mining is historically superimposed upon strong regional wetland effects, producing a combined elevation of both THg and MeHg in the Western Upper Peninsula.